Orality and Irony in the Fictional Trials of Cantinflas, Tres Patines, and Tequilas (Andamios, Revista de Investigación Social, 2025)
This article explores orality and irony as discursive tools in fictional judicial contexts through a comparative analysis of three iconic characters: el Tequilas (from the novel El circo que se perdió en el desierto de Sonora by Miguel Méndez), Tres Patines (from the radio series La Tremenda Corte), and Cantinflas (from the film Ahí está el detalle). The concept of oral genres is redefined to transcend its ephemerality, and acknowledge its performative function and capacity for mediation and fictionalization. The study examines how these characters utilize peculiar language, humor, and satire to subvert the solemnity of the judicial system, expose its contradictions, and forge a form of cultural resistance. It analyzes orality as a battleground where mischief and irony expose social archetypes and challenge power, offering a re-signification of the popular voice against established structures.
Keywords: Orality; irony; oral genres; satire; popular culture